Pre-Descemet's endothelial keratoplasty: a simple, Descemet's membrane scoring technique for successful graft preparation. Issue 6 (17th February 2021) - Pereira, Nicolas Cesario; Forseto, Adriana dos Santos; Maluf, Rafaela Cesario Pereira; Dua, Harminder Singh
Abstract : Purpose: Pre-Descemet's endothelial keratoplasty (PDEK) donor tissue preparation involves the intrastromal injection of air to create a type 1 big bubble (BB) and avoidance of the creation of a type 2 BB. The purpose of this study was to design and test a technique to consistently creates a type 1 BB without risk of creating a type 2 BB. Methods: A prospective matched study with 64 human donor sclerocorneal discs, which were not suitable for corneal transplantation, was conducted. The corneas were divided into two groups, of which 32 were subjected to the standard technique of preparing the PDEK donor tissue (group 1, control) and 32 new technique, where in the donor Descemet's membrane was scored with a Sinskey hook. Frequency of occurrence of different types of BB was compared and statistically analysed. Results: With the standard technique (group 1), type 1 BB occurred in 53.1%, type 2 BB in 34.4% and mixed BB in 12.5% of samples. With the scoring technique (group 2), a type 1 BB occurred in 100% of the samples. No type 2 or mixed BB occurred in any case in group 2. The difference in creation of a type 1BB between the two groups was statistically significant (p=0.00). Conclusion: The scoring technique is a simple, inexpensive and reproducible option to consistently achieve a type 1 BB to prepare PDEK graft tissue. The next step would be to study the clinical outcomes of PDEK performed with tissue obtained by the scoring technique.